Managing science-policy interfaces for impact: Interactions within the environmental governance meshwork. Issue 113 (November 2020) - Sarkki, Simo; Balian, Estelle; Heink, Ulrich; Keune, Hans; Nesshöver, Carsten; Niemelä, Jari; Tinch, Rob; Van Den Hove, Sybille; Watt, Allan; Waylen, Kerry A.; Young, Juliette C.
Highlights: Science-policy interface organizations (SPIORGs) have complex links with context. A "governance meshwork" approach can help structure analysis of links with context. We illustrate application of this approach using five divergent cases of SPIORGs. We identify ten aspects of governance meshwork with varying linkages to SPIORGs. Deliberate attention to context will enhance SPIORGs' ability to achieve impact. Abstract: Science-policy interface organizations and initiatives (SPIORG) are a key component of environmental governance designed to make links between science and society. However, the sciencepolicy interface literature lacks a structured approach to explaining the impacts of context on and by these initiatives. To better understand these impacts on and interactions with governance, this paper uses the concept of the governance 'meshwork' to explore how dynamic processes – encompassing prior, current and anticipated interactions – coproduce knowledge and impact via processes, negotiation and networking activities at multiple governance levels. To illustrate the interactions between SPIORGs and governance meshwork we use five cases representing archetypal SPIORGs. These cases demonstrate how all initiatives and organizations link to their contexts in complex and unique ways, yet also identifies ten important aspects that connect the governance meshwork to SPIORGs. These aspects of the meshwork, together with the typology of organizations, provide a comprehensive framework that can help make sense how the SPIORGs are embedded in the surrounding governance contexts. We highlight that SPIORGs must purposively consider and engage with their contexts to increase their potential impact on knowledge co-production and policy making.